2019
DOI: 10.11144/javeriana.sc24-2.ccao
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituent analysis of the Babassu (Orbignya phalerata Mart.) mesocarp

Abstract: The Babassu nut (Orbignya phalerata Mart.) mesocarp is traditionally transformed to flour and consumed in some Brazilian areas for its attributed medicinal activity; however, its chemical properties remain to be elucidated. The present work aimed at analyzing the babassu mesocarp phytochemical constituents. Babassu nut samples were collected in the Brazilian Amazon, and their mesocarps were prepared and macerated in different solvents. The chromatographic fractionation of selected methanol extracts yielded thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Oil seed covers significant quantities of polyunsaturated fatty acids (PUFA) 46,47 but also minor amounts of (poly)phenols, tri-, diglycerides, terpenes, and phytosterols. 48 Table 1 shows some babassu derivatives rich in phytochemicals reviewed in this work based on the preparation method and there is an overview of the primary class of phytochemicals screened in studies. This table is quite revealing in several ways.…”
Section: Primary and Secondary Metabolites In Babassu (A Speciosa Syn...mentioning
confidence: 99%
“…Oil seed covers significant quantities of polyunsaturated fatty acids (PUFA) 46,47 but also minor amounts of (poly)phenols, tri-, diglycerides, terpenes, and phytosterols. 48 Table 1 shows some babassu derivatives rich in phytochemicals reviewed in this work based on the preparation method and there is an overview of the primary class of phytochemicals screened in studies. This table is quite revealing in several ways.…”
Section: Primary and Secondary Metabolites In Babassu (A Speciosa Syn...mentioning
confidence: 99%
“…Babassu mesocarp is a low-cost material obtained as a by-product of the babassu coconut, a native species in Brazil widely distributed in the northern and northeastern regions of the country, especially in the state of Maranhão [ 11 ]. It is mainly composed of starch (68.3%), but also contains fibers and amino acids (2.51%), proteins (1.54%), soluble carbohydrates (1.25%), and lipids (0.27%) [ 12 ]. Studies have shown that babassu mesocarp has antimicrobial action due to its phytochemical composition of polyphenols and phenolic compounds [ 13 ].…”
Section: Introductionmentioning
confidence: 99%